A new species of Catasetum (Cymbidieae, Epidendroideae, Orchidaceae) from the Southern region of the Brazilian Amazon - Benelli, Adarilda Petini; Soares-Lopes, Célia Regina Araújo (Phytotaxa, 2015)
A new species of Catasetum has been found along the banks of the River Teles Pires, in the Southern region of the Brazilian Amazon. In the present study it is described and illustrated, and has its conservation status discussed. The species presents unique features and stands out among others found in the same region, and can be compared partially to C. mattosianum.